Hubungan Tingkat Kecemasan dengan Kualitas Tidur pada Pasien Kanker yang Menjalani Kemoterapi di RSUD Dr. Adhyatma Semarang - Ajeng Maharani; Dwi Retnaningsih; Emilia Puspitasari (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Cancer is a chronic disease that remains a major health problem and can cause physical and psychological effects, one of which is anxiety, especially in patients undergoing chemotherapy. Uncontrolled anxiety can affect the patient's sleep quality. To determine the relationship between anxiety levels and sleep quality in cancer patients undergoing chemotherapy at Dr. Adhyatma Tugu Regional General Hospital in Semarang. This quantitative study used a descriptive correlational design and a cross-sectional approach. The sample consisted of 73 respondents using purposive sampling. The instruments used were the Hamilton Rating Scale for Anxiety (HARS) and the Pittsburgh Sleep Quality Index (PSQI). The results showed that most respondents experienced moderate anxiety (57.5%) and very poor sleep quality (60.3%). Spearman's rho test showed a strong and significant relationship between anxiety levels and sleep quality (r = 0.724; p < 0.05). There is a strong and significant relationship between anxiety levels and sleep quality in cancer patients undergoing chemotherapy at Dr. Adhyatma, MPH Tugu Semarang Regional General Hospital (r = 0.724; p < 0.05).